Thermal insulation mortar board and preparation method thereof
By using compositions with specific component proportions in the insulation mortar board, the existing insulation mortar materials have been solved, and efficient insulation and good mechanical properties are achieved. It is suitable for direct exposed use without additional protective layers.
Patent Information
- Application Number
- CN202411868208.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing insulation mortar materials use a large amount of lightweight materials, which are low in density and poor in hardness, are complex in construction and are easy to fall off, which affects safety, and lacks decorativeness and requires additional protective layers.
The thermal insulation mortar board is prepared using a composition containing components A and B. Component A contains fillers, polypropylene fibers, aluminum powder, alkaline agents, organic foaming agents, thermal insulation materials and light reflectors. Component B contains solid resin, ammonia water, styrene acrylic emulsion, silicon sol and water. The bonding strength is improved through the synergistic effect of aluminum powder and alkaline agents to form a three-dimensional network hollow structure with low thermal conductivity.
It realizes excellent thermal insulation and thermal insulation ability and good mechanical properties of the insulation mortar board, is easy to apply, has a thickness of only 4-6mm, is high in safety and does not require an additional protective layer.
Smart Images

Figure BDA0005195045050000141 
Figure BDA0005195045050000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building thermal insulation, and in particular to a thermal insulation mortar board and a preparation method thereof. Background Art
[0002] In recent years, the thermal insulation and heat preservation of buildings have received more and more attention. Thermal insulation and heat preservation can not only improve the energy utilization efficiency of buildings and reduce energy consumption, but also improve the living environment and enhance the comfort of residents. At present, the most common thermal insulation material for building exterior walls is exterior wall thermal insulation mortar, which uses the principle of bubble insulation and adds a certain amount of thermal insulation materials and admixtures. It has good thermal insulation performance and reduces energy consumption. Compared with ordinary mortar, exterior wall thermal insulation mortar can better maintain indoor temperature and reduce the impact of cold and hot bridges on the interior.
[0003] Ordinary thermal insulation mortar materials use a lot of lightweight materials and need to be thickly applied during use. In addition, thermal insulation mortar is not decorative and requires a protective layer. For example, after the thermal insulation mortar is applied to the exterior wall, it is necessary to lay tiles or apply exterior wall paint. Therefore, further research on thermal insulation mortar materials is still needed to improve its performance and ease of application. Summary of the invention
[0004] In view of this, the present invention proposes a thermal insulation mortar board and a preparation method thereof, wherein the thermal insulation mortar board has excellent thermal insulation capabilities and good mechanical properties; at the same time, it is easy to use and has high safety.
[0005] The present invention provides the following technical solutions:
[0006] A thermal insulation mortar board is prepared from a composition comprising a component A and a component B; wherein the component A comprises 35-88% of a filler, 2-10% of polypropylene fiber, 2-8% of aluminum powder, 5-15% of an alkaline agent, 1-4% of an organic foaming agent, 6-27% of a thermal insulation material, and 8-30% of a light reflector, based on the total weight of the component A; the component B comprises 1-8% of a solid resin, 9-22% of aqueous ammonia, 18-40% of a styrene-acrylic emulsion, 10-32% of a silica sol, 18-39% of water, and 0.25-2.7% of other functional additives, based on the total weight of the component B; wherein the weight ratio of the component A to the component B is 1:(1-2).
[0007] Optionally, the weight ratio of the thermal insulation material content to the sum of the solid resin and the styrene-acrylic emulsion content is 1:(1-2).
[0008] Optionally, the thermal insulation material comprises SiO2 aerogel and wood chips; the specific surface area of the SiO2 aerogel is 200-1000m 2 / g, the porosity is 80-99.8%; the average particle size of the sawdust is 48-80 meshes.
[0009] Optionally, the filler includes one or more of quartz powder, calcium carbonate, and magnesium carbonate.
[0010] Optionally, the filler comprises 15-35% quartz powder and 15-35% calcium carbonate, based on the weight of the A component.
[0011] Optionally, the aluminum powder includes one or more of aluminum oxide or aluminum silicate, and the average particle size thereof is 400-600 mesh; other functional additives include 0.2-1% of a leveling agent, 0.05-1.2% of a preservative, and 0.02-0.5% of a thickener, based on the total weight of component B.
[0012] Optionally, the glass transition temperature of the solid resin is 30° C. to 85° C.; the solid resin is one or more of acrylic resin, polyurethane resin, and epoxy resin.
[0013] Optionally, the thickness of the thermal insulation mortar board is 4-6 mm.
[0014] Optionally, a decorative layer is further provided on the surface of the thermal insulation mortar board; the decorative layer comprises 0.5-10% color paste, 85-99.5% styrene acrylic emulsion, 0.01-1% thickener, 0.05-0.9% defoamer, and 0-1% preservative, based on the weight of the decorative layer.
[0015] The present invention also provides a method for preparing the thermal insulation mortar board as described above, which comprises the following steps: 1) mixing filler, polypropylene fiber, aluminum powder, alkaline agent, organic foaming agent, thermal insulation material, and light reflector to obtain component A; 2) mixing solid resin with ammonia water until the solid resin is completely dissolved to obtain a solid resin aqueous solution; mixing the obtained solid resin aqueous solution, styrene-acrylic emulsion, other functional additives, silica sol, and water to obtain component B; 3) mixing component A and component B evenly to obtain a composition comprising component A and component B; 4) injecting the composition obtained in step 3) into a mold, drying the mold, and obtaining a thermal insulation mortar board.
[0016] According to the technical solution of the present invention, the thermal insulation mortar board contains specific contents of each component, so that the thermal insulation mortar board has excellent thermal insulation ability and good mechanical properties; at the same time, it is easy to use and has high safety. Specifically, in the thermal insulation mortar board, the synergistic effect of aluminum powder and alkaline agent can improve the bonding strength between the components, SiO2 aerogel, wood chips, organic styrene acrylic emulsion, reflective insulation agent and the formed bubbles and / or pores are connected together to form a three-dimensional network hollow structure, with extremely low thermal conductivity, which can effectively prevent heat conduction and has excellent thermal insulation; at the same time, the thermal insulation mortar board has excellent mechanical properties. DETAILED DESCRIPTION
[0017] For ease of understanding of the present invention, the present invention will be described more fully below with reference to examples. Preferred embodiments of the present invention are provided in the examples. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0018] At present, a large amount of lightweight particles are added to the thermal insulation mortar, which makes its density low, its hardness poor, and it is easily damaged by the outside world. The mortar itself is not decorative and has low strength. After construction, a decorative protective layer needs to be applied. For example, after the thermal insulation mortar is applied to the exterior wall, tiles need to be laid or exterior wall paint needs to be applied. In order to achieve the desired thermal insulation effect, the thermal insulation mortar needs to be applied thickly by 2-3 cm. Generally, it needs to be applied in 2-3 times to reach the required thickness. The construction is complicated, and it is easy to hollow, crack, and fall off, which may cause safety accidents. The thermal insulation mortar board of the embodiment of the present invention can further improve the above-mentioned shortcomings. It has excellent thermal insulation ability and extremely low thermal conductivity. At the same time, the thickness of the thermal insulation mortar board is only 4-6 mm, and it can be firmly fixed on the surface of the building using tile adhesive, and it will not fall off and cause safety accidents. Specifically, in the thermal insulation mortar board of the embodiment of the present invention, the synergistic effect of aluminum powder and alkaline agent can improve the bonding strength between the components, and the thermal insulation material, organic styrene acrylic emulsion, light reflector and the formed bubbles and / or pores are connected together to form a three-dimensional network hollow structure with extremely low thermal conductivity, which can effectively prevent heat conduction and has excellent thermal insulation; at the same time, the thermal insulation mortar board has excellent mechanical properties.
[0019] In an embodiment of the present invention, the thermal insulation mortar board is prepared from a composition comprising component A and component B: component A comprises 35-88%, for example 45-55%, of filler, 2-10%, for example 4-6%, of polypropylene fiber, 2-8%, for example 4-6%, of aluminum powder, 5-15%, for example 7-8%, of alkaline agent, 1-4%, for example 1-2.5%, of organic foaming agent, 6-27%, for example 15-21%, of thermal insulation material, 8-30%, for example 10-20%, of light reflector, base Based on the total weight of component A; component B includes 1-8%, such as 2-4%, of solid resin, 9-22%, such as 10-20%, of ammonia water, 18-40%, such as 25-35%, of styrene-acrylic emulsion, 10-32%, such as 15-25%, of silica sol, 18-39%, such as 20-35%, of water, and 0.25-2.7%, such as 0.5-1.5%, of other functional additives, based on the total weight of component B; wherein the weight ratio of component A to component B is 1:(1-2). Those skilled in the art should understand that the components in component B do not have to be used together with the components in component B, but can also be used together with the components in component A, and the use of all components can be selected according to needs.
[0020] The weight ratio of the sum of the contents of SiO2 aerogel and wood chips to the sum of the contents of solid resin and styrene acrylic emulsion is 1:(1-2), for example 1:1.6.
[0021] The filler may include one or more of quartz powder, calcium carbonate, and magnesium carbonate; the filler may include 15-35%, such as 20-30%, of quartz powder, and 15-35%, such as 20-30%, of calcium carbonate, based on the weight of component A. Quartz powder is quartz powder well known in the art, also known as white sand powder; the average particle size is 600-800 mesh; in the quartz powder, the content of silicon dioxide is 80-99%, such as 98%, based on the weight of the quartz powder. Calcium carbonate may include light calcium carbonate or heavy calcium carbonate (also known as heavy calcium), such as heavy calcium carbonate; the average particle size of calcium carbonate is generally 200-600 mesh, such as 200-400 mesh, such as 200 mesh.
[0022] Polypropylene fiber is a synthetic fiber spun from polypropylene as raw material, and its fiber length can be 2-8mm, such as 4-7mm, such as 6mm; it increases the toughness of the mortar board coating and reduces the damage to the mortar board caused by external impact.
[0023] Aluminum powder may generally include one or more of aluminum oxide or aluminum silicate, and the average particle size may be 400-600 mesh; the aluminate gel substance produced by the aluminum ions in the aluminum powder and the alkali in the composition, such as calcium hydroxide, can bond the components during the solidification process of the mortar board, increase the bonding strength between the components, and thus improve the mechanical strength of the thermal insulation mortar board.
[0024] The alkaline agent is a metal hydroxide, such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, etc. The organic foaming agent is usually a powdered foaming agent well known to those skilled in the art, such as usually one or more of sodium alkylbenzene sulfonate such as sodium dodecylbenzene sulfonate and sodium alkyl sulfate.
[0025] The thermal insulation material includes one or more of SiO2 aerogel and wood chips. Usually, the thermal insulation material may include 4-17% SiO2 aerogel and 2-10% wood chips, based on the total weight of component A. SiO2 aerogel is a nanoporous solid material with low thermal conductivity, low density, large specific surface area, high porosity, and small pores. The thermal conductivity of SiO2 aerogel at room temperature can be as low as 0.012W / (m·k), and the density can be as low as 3kg / m 3 , with a specific surface area of 200-1000m 2 / g, porosity up to 80-99.8%, pore size of 1-100nm. The average particle size of wood chips can be 48-80 mesh; wood chips are loose and have a tiny pore structure, which can reduce thermal conductivity and thus slow down heat transfer.
[0026] Light reflectors include mica powder, titanium dioxide, zirconium oxide, pearl powder, aluminum silver paste, hollow glass microspheres, etc. The average particle size of mica powder is 600-800 mesh, and it is usually in a flaky structure. It can offset the shrinkage stress of the thermal insulation mortar board during the film forming process, reduce cracking, and have a good light reflection effect. Titanium dioxide can be a rutile titanium dioxide with an average particle size of 1200-1500 mesh. The light reflector can include 5-18% of mica powder and 3-10% of titanium dioxide, based on the total weight of component A.
[0027] The glass transition temperature of the solid resin is 30°C to 85°C; the solid resin is generally one or more of an acrylic resin, a polyurethane resin, and an epoxy resin. The number average molecular weight (Mn) of the solid resin is 2000-9000 g / mol, as determined by gel permeation chromatography. The acrylic resin may be a water-based acrylic solid resin J678 purchased from BASF Chemical Company; the polyurethane resin may be a 8355 water-based polyurethane emulsion purchased from Wanhua Chemical Group Co., Ltd. At room temperature and pressure, the concentration of the ammonia water used is generally 20-25%, based on the weight of the ammonia water.
[0028] Styrene-acrylic latex is an anionic latex copolymerized by styrene and acrylate, etc., with a glass transition temperature of 15-18°C and a solid content of 40-60%, such as 40-50%, such as 45-47%; the styrene-acrylic latex may include epoxy-modified styrene-acrylic latex, silicone-modified styrene-acrylic latex, and organic fluorine-modified styrene-acrylic latex. The styrene-acrylic latex bonds the various components and improves the flexibility and gloss of the thermal insulation mortar board.
[0029] Other functional additives may include 0.2-1% of a leveling agent, 0.05-1.2% of a preservative, and 0.02-0.5% of a thickener, based on the total weight of component B. The leveling agent is usually an acrylic acid, such as a polyacrylate solution; or a silicone leveling agent, such as polydimethylsiloxane or polymethylphenylsiloxane. The preservative includes at least one of kason, benzisothiazolinone (BIT), etc. The thickener may be any commonly used thickener known to those skilled in the art, such as a polyurethane thickener, which can increase the viscosity of the liquid and avoid stratification.
[0030] Silica sol is a uniform and stable dispersion of amorphous, nano-sized silica particles in water or organic solvents. The particle size distribution range of silica particles is usually 3-150μm, such as 9-20μm; the solid content of silica sol is 20-32%. Fine-particle silica sol reacts with alkali to form silicate gel material to bond various components, thereby improving the hardness of the mortar board.
[0031] Optionally, the thermal insulation mortar board is prepared from a composition comprising component A and component B, wherein component A comprises 15-35% such as 25% quartz powder, 2-10% such as 5% polypropylene fiber, 2-8% such as 5% aluminum powder, 5-15% such as 8% calcium hydroxide, 1-4% such as 2% organic foaming agent, 15-35% such as 25% heavy calcium carbonate, 4-17% such as 10% SiO2 aerogel, 2-10% such as 5% wood chips, 5-18% such as 5-10% mica powder, 3-10% such as 3-6% titanium dioxide, based on the total weight of component A; Component B includes 1-8%, for example 2-4%, of solid resin, 9-22%, for example 16%, of 20% ammonia water, 18-40%, for example 30%, of styrene-acrylic emulsion, 0.2-1%, for example 0.5%, of leveling agent, 0.05-1.2%, for example 0.4%, of preservative, 10-32%, for example 20%, of silica sol, 18-39%, for example 29%, and 0.02-0.5%, for example 0.1%, of thickener, based on the total weight of component B; wherein the weight ratio of component A to component B is 1:(1-2), for example 1:(1-1.5), for example 1:(1.1-1.3).
[0032] The surface of the thermal insulation mortar board may also be provided with a decorative layer containing various desired patterns or colors, so that it has the same decorative properties as tiles and can be directly exposed for use without adding a protective layer.
[0033] The decorative layer comprises 0.5-10% such as 2% color paste, 85-99.5% such as 97.5% styrene acrylic emulsion, 0.01-1% such as 0.2% thickener, 0.05-0.9% such as 0.2% defoamer, 0-1% such as 0.1% preservative, based on the weight of the decorative layer. The sum of the contents of the various components of the decorative layer is 100%, based on the weight of the decorative layer. The type of color paste can be selected as needed. Styrene acrylic emulsion, thickener, preservative are as defined in component B. The styrene acrylic emulsion, thickener, preservative used in the decorative layer can be the same as or different from those in component B.
[0034] The color paste may be any type of color paste commonly used in the art that has excellent weather resistance and light resistance, such as iron-based color pastes (yellow, red and black) and phthalocyanine-based color pastes.
[0035] The defoamer may include one or more of an organosilicon defoamer and a mineral oil defoamer. Common organosilicon defoamers are usually prepared by taking silicone oil as a base component and mixing a suitable solvent, an emulsifier or an inorganic filler. Mineral oil defoamers are usually prepared by using mineral oil, inorganic hydrophobic particles and an emulsifier as the main defoaming ingredients. The organosilicon defoamer may be selected from the brand 105509 purchased from Guangzhou Kefeng Chemical Co., Ltd. and the brand CI-0560 purchased from Guangdong Nanhui New Materials Co., Ltd.; the mineral oil defoamer may be the brand B-638 purchased from Guangdong Zhongke Hongtai New Materials Co., Ltd.
[0036] In this embodiment, the "average particle size" of all solid particles included in the composition refers to the mesh size corresponding to a cumulative weight percentage on the sieve of 50%, which is measured by a mechanical method according to GB / T 21524-2008.
[0037] In an embodiment of the present invention, the method for preparing the above-mentioned thermal insulation mortar board includes the following steps: 1) mixing filler, polypropylene fiber, aluminum powder, alkaline agent, organic foaming agent, thermal insulation material, and light reflector to obtain component A; 2) mixing solid resin with ammonia water until the solid resin is completely dissolved to obtain a solid resin aqueous solution; mixing the obtained solid resin aqueous solution, styrene-acrylic emulsion, silica sol, water, and other functional additives to obtain component B; 3) mixing component A and component B evenly to obtain a composition comprising component A and component B; 4) injecting the composition obtained in step 3) into a mold, drying the mold, and obtaining a thermal insulation mortar board.
[0038] Optionally, the method for preparing the thermal insulation mortar board comprises the following steps:
[0039] 1) quartz powder, mica powder, polypropylene fiber, aluminum powder, calcium hydroxide, organic foaming agent, heavy calcium carbonate, SiO2 aerogel, sawdust and titanium dioxide are mixed to obtain component A;
[0040] 2) mixing the solid resin with ammonia water until the solid resin is completely dissolved to obtain a solid resin aqueous solution; mixing the obtained solid resin aqueous solution, styrene acrylic emulsion, leveling agent, silica sol, water, thickener, and preservative to obtain component B;
[0041] 3) mixing component A and component B uniformly to obtain a composition comprising component A and component B;
[0042] 4) injecting the composition obtained in step 3) into a mold, drying the mold, and obtaining a thermal insulation mortar board.
[0043] Step 1) includes putting the above-mentioned quartz powder, mica powder, polypropylene fiber, aluminum powder, calcium hydroxide, organic foaming agent, heavy calcium carbonate, SiO2 aerogel, sawdust, and titanium dioxide into a dry powder stirring kettle, stirring at a stirring rate of 300-600r / min for 10-40min, for example, 20min, so that the ingredients are evenly mixed to obtain component A.
[0044] Step 2) includes adding solid resin and 20% ammonia water into a dispersion kettle, dispersing for 60-80 minutes at a stirring rate of 800-1000r / min, ensuring that the temperature of the ammonia water is not lower than 50°C during the dispersion, until the solid resin is completely dissolved and cooled to room temperature, to obtain a solid resin aqueous solution, wherein the solid content of the solid resin aqueous solution is 20-50%, such as 30%, based on the weight of the solid resin aqueous solution; wherein the weight ratio of the solid resin to the 20% ammonia water is 1: (2-8), such as 1: 4. The obtained solid resin aqueous solution, styrene-acrylic emulsion, leveling agent, silica sol, water, thickener, and preservative are added to a dispersion kettle, and stirred at a stirring rate of 600-800r / min for 10-40min, such as 20min, so that the components are evenly mixed to obtain component B.
[0045] Step 4) comprises brushing the mold with an oily release agent such as engine oil, injecting the composition obtained in step 3) into the mold, and after the composition is evenly leveled and reaches a thickness of 5-8 mm, baking the mold at a temperature of 80-100° C. until a mortar board with a water content of less than 1.0% is formed, and cooling the mortar board to 30-60° C., for example, 40° C., to obtain a thermal insulation mortar board with a thickness of 4-6 mm.
[0046] In an embodiment of the present invention, the method for preparing the above-mentioned thermal insulation mortar board with decorative function also includes mixing styrene acrylic emulsion, color paste, defoamer, and thickener to obtain component C; coating component C on the surface of the above-mentioned thermal insulation mortar board to form a desired pattern or color, and then drying the coated thermal insulation mortar board, for example, baking at a temperature of 60-70°C for 20-50min, for example, 30min, to obtain a thermal insulation mortar board with decorative function.
[0047] Mixing the styrene acrylic emulsion, color paste, defoamer and thickener includes adding the styrene acrylic emulsion, color paste, defoamer and thickener into a dispersion kettle, stirring at a stirring rate of 600-800 r / min for 10-40 min, for example, 20 min, to obtain component C.
[0048] The construction method of the thermal insulation mortar board according to the embodiment of the present invention includes bonding the thermal insulation mortar board to the surface of the building using tile adhesive, for example, the tile adhesive meets the requirements of JCT 547-2017C1.
[0049] Optionally, the thermal insulation mortar board construction method includes:
[0050] i) Clean the surface of the building, such as removing weathering, putty, paint, grease, wax, dirt, looseness and any mold, microorganisms or algae on the surface of the building, repairing holes and cracks, and chiseling and leveling the hollow parts;
[0051] ii) firstly evenly apply tile adhesive on the surface of the building, and at the same time, apply tile adhesive on the back of the thermal insulation mortar board of the embodiment of the present invention, and then stick the thermal insulation mortar board on the surface of the building; evenly bond and fix the mortar board to ensure that the thermal insulation mortar board does not slip;
[0052] iii) The newly pasted mortar board cannot be washed or damaged by rainwater; it cannot be stepped on or otherwise damaged by the paint film within 48 hours after pasting; the room temperature during winter construction should not be lower than 5℃.
[0053] The present invention is described below by specific examples. The examples described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0054] raw material
[0055] Quartz powder: purchased from Sichuan Nanlian Environmental Resources Technology Co., Ltd., with an average particle size of 600 mesh (25 μm) and a Mohs hardness of 7.5;
[0056] Mica powder: purchased from Anhui Ge Rui New Material Technology Co., Ltd., GB-2 type, average particle size 600 mesh;
[0057] Polypropylene fiber: Shandong Baiyou Engineering Materials Co., Ltd., fiber length 6mm;
[0058] Aluminum powder: Alumina, average particle size 500 mesh (30 μm), purchased from Hebei Kuoxiang Alloy Material Co., Ltd.;
[0059] Calcium hydroxide: purchased from Jinan Longteng Chemical Co., Ltd., model 14-2-8;
[0060] Foaming agent: Foshan Daping Chemical Technology Co., Ltd., sodium dodecylbenzene sulfonate LAS-70;
[0061] Heavy calcium: The average particle diameter is 200 mesh (74 μm), purchased from Jiaoling Jinpeng Fine Chemical Co., Ltd.
[0062] SiO2 aerogel: Jinyuan Mine Industry Processing Plant, Lingshou County, Hebei Province, models 2223 and 336; specific surface areas are 200m 2 / g、1000m2 / g;
[0063] Sawdust: Nanchang Jiahong Wood Powder Co., Ltd., average particle size is 48 mesh;
[0064] Titanium dioxide: model R-215, purchased from Huizhou Biaozhou Industrial Co., Ltd., with an average particle size of 1250 mesh (10 μm);
[0065] Solid resin: purchased from BASF (China) Co., Ltd., water-based acrylic resin, model J678, Tg of 85°C, molecular weight (Mn) of 8600 g / mol;
[0066] Styrene acrylic emulsion type I: purchased from Foshan Shunde Badfu Industrial Co., Ltd., model 6607, Tg is 16 ° C, solid content is 45wt%;
[0067] Styrene acrylic emulsion type II: purchased from Foshan Shunde Badfu Industrial Co., Ltd., model 6992A, Tg is 18 ° C, solid content is 47wt%;
[0068] Leveling agent: BYK Chemical Company, Germany, model BYK-358N;
[0069] Silica sol: Taizhou Xiesheng Precision Casting Technology Co., Ltd., model GRJ30, the particle size distribution range of silica particles is 9-20μm;
[0070] Color paste: Guangzhou Kedi Color Paste Co., Ltd., red iron-based color paste;
[0071] Thickener: Polyurethane thickener, model N-2253, purchased from Foshan Shenghui New Materials Co., Ltd.
[0072] Preservative: Kasong, purchased from Foshan Lanfeng Additive Co., Ltd.
[0073] Example 1
[0074] Before starting work, clean the pipelines, dispersers, packaging machines and other production equipment.
[0075] 1. Put quartz powder, mica powder, polypropylene fiber, aluminum powder, calcium hydroxide, foaming agent, heavy calcium, SiO2 aerogel, sawdust and titanium dioxide into a dry powder mixing kettle according to the amount described in Table 1, stir at 500r / min for 20min to obtain component A, and set aside after passing the central control test;
[0076] 2. Put the solid resin in the amount described in Table 1 and 20% ammonia water into a dispersion kettle, start the dispersion kettle, and disperse for 70 minutes at a stirring rate of 1000r / min. During the dispersion, ensure that the temperature of the ammonia water is not lower than 50°C until the solid resin is completely dissolved to obtain a solid resin aqueous solution, and cool it to room temperature for use;
[0077] The obtained solid resin aqueous solution and the styrene acrylic emulsion, leveling agent, silica sol, water, thickener and preservative in the amounts described in Table 1 were added to a dispersion kettle and stirred at 700 r / min for 20 min to obtain component B. After passing the central control test, it was set aside.
[0078] 3. Mix component A / component B in a mass ratio of 1:1.2 to obtain a composition; inject the composition into a mold with a specification of 30 cm×60 cm. The mold has been coated with engine oil before adding the composition, so that the thickness of the composition in the mold is 5.5 mm. After the mortar is evenly leveled, the mold is sent to a 100°C environment and baked for 100 minutes until the water content in the mortar board is less than 1.0%, and then the temperature is reduced to 40°C to obtain a mortar board with a thickness of 4.8 mm.
[0079] The specific compositions of the mortar boards are summarized in Tables 1 and 2.
[0080] Examples 2-7 and Comparative Examples 1-6
[0081] The steps of Example 1 were repeated, except that the content and type of each component in each component were adjusted, as shown in Tables 1 and 2 for details.
[0082] Example 8
[0083] The steps of Example 1 were repeated, except that component C was coated on the surface of the mortar board obtained in Example 1, and then baked at 65°C for 30 minutes to obtain a decorative thermal insulation mortar board with a red surface; wherein component C included 2 parts by weight of red iron-based color paste, 97.5 parts by weight of type II styrene-acrylic emulsion, 0.2 parts by weight of thickener, 0.2 parts by weight of defoamer, and 0.1 parts by weight of preservative. The properties of the obtained decorative thermal insulation mortar board are shown in Table 3.
[0084] Table 1 Composition of component A of the thermal insulation mortar board of Examples 1-7 and Comparative Examples 1-6
[0085]
[0086] Table 2 Composition of component B of the thermal insulation mortar board of Examples 1-7 and Comparative Examples 1-6 and weight ratio of A to B
[0087]
[0088] Performance Testing
[0089] The mortar boards of the embodiments and comparative examples were subjected to performance tests according to the requirements of GBT 20473-2006 Type II.
[0090] In addition, the pencil hardness of the mortar boards of the embodiments of the present invention tested according to GB / T6739-2006 all reached 3HB level, which fully meets the hardness requirement for exposed use. The test results are summarized in Table 3.
[0091] Table 3 Performance test of mortar boards of various embodiments and comparative examples
[0092] serial number Compressive strength / MPa Thermal conductivity / (W / (m·K)) Linear shrinkage / % Example 1 17.6 0.063 0.18 Example 2 16.0 0.058 0.19 Example 3 17.2 0.073 0.2 Example 4 17.1 0.081 0.2 Example 5 16.5 0.057 0.19 Example 6 16.1 0.073 0.18 Example 7 15.9 0.071 0.19 Example 8 17.6 0.063 0.18 Comparative Example 1 15.6 0.116 0.2 Comparative Example 2 15.5 0.098 0.19 Comparative Example 3 15.2 0.091 0.21 Comparative Example 4 14.1 0.087 0.25 Comparative Example 5 13.4 0.09 0.22 Comparative Example 6 13.2 0.094 0.32
[0093] According to the technical solution of the embodiment of the present invention, the thermal conductivity of the thermal insulation mortar board is very low, so it has excellent thermal insulation capabilities; and its compressive strength is high and the linear shrinkage rate is low, and it has a hardness of 3HB grade. Therefore, the thermal insulation mortar board has excellent mechanical properties such as strength, hardness and dimensional stability; at the same time, it has a small thickness, is easy to use, and has high safety.
[0094] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions may occur depending on design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A thermal insulation mortar board, characterized in that: Prepared from a composition comprising component A and component B; wherein, Component A includes 35-88% filler, 2-10% polypropylene fiber, 2-8% aluminum powder, 5-15% alkaline agent, 1-4% organic foaming agent, 6-27% thermal insulation material, and 8-30% light reflector, based on the total weight of component A; Component B includes 1-8% solid resin, 9-22% ammonia water, 18-40% styrene acrylic emulsion, 10-32% silica sol, 18-39% water, and 0.25-2.7% other functional additives, based on the total weight of component B; The weight ratio of component A to component B is 1:(1-2).
2. The thermal insulation mortar board according to claim 1, characterized in that: The weight ratio of the thermal insulation material content to the sum of the solid resin and the styrene-acrylic emulsion content is 1:(1-2).
3. The thermal insulation mortar board according to claim 1 or 2, characterized in that: The thermal insulation material comprises SiO2 aerogel and wood chips; the specific surface area of the SiO2 aerogel is 200-1000m 2 / g, the porosity is 80-99.8%; the average particle size of the sawdust is 48-80 meshes.
4. The thermal insulation mortar board according to claim 1 or 2, characterized in that: The filler includes one or more of quartz powder, calcium carbonate and magnesium carbonate.
5. The thermal insulation mortar board according to claim 4, characterized in that: The filler comprises 15-35% of quartz powder and 15-35% of calcium carbonate, based on the weight of the A component.
6. The thermal insulation mortar board according to claim 1 or 2, characterized in that: The aluminum powder includes one or more of aluminum oxide or aluminum silicate, and its average particle size is 400-600 meshes; other functional additives include 0.2-1% of leveling agent, 0.05-1.2% of preservative, and 0.02-0.5% of thickener, based on the total weight of component B.
7. The thermal insulation mortar board according to claim 1 or 2, characterized in that: The glass transition temperature of the solid resin is 30° C. to 85° C.; the solid resin is one or more of acrylic resin, polyurethane resin, and epoxy resin.
8. The thermal insulation mortar board according to claim 1 or 2, characterized in that: The thickness of the thermal insulation mortar board is 4-6 mm.
9. The thermal insulation mortar board according to claim 1 or 2, characterized in that: The surface of the thermal insulation mortar board is also provided with a decorative layer; the decorative layer comprises 0.5-10% color paste, 85-99.5% styrene acrylic emulsion, 0.01-1% thickener, 0.05-0.9% defoamer, and 0-1% preservative, based on the weight of the decorative layer.
10. A method for preparing the thermal insulation mortar board according to any one of claims 1 to 9, characterized in that: The steps include: 1) mixing filler, polypropylene fiber, aluminum powder, alkaline agent, organic foaming agent, heat insulating material and light reflective agent to obtain component A; 2) mixing the solid resin with ammonia water until the solid resin is completely dissolved to obtain a solid resin aqueous solution; mixing the obtained solid resin aqueous solution, styrene acrylic emulsion, other functional additives, silica sol and water to obtain component B; 3) mixing component A and component B uniformly to obtain a composition comprising component A and component B; 4) injecting the composition obtained in step 3) into a mold, and drying the mold to obtain a thermal insulation mortar board.
Citation Information
Patent Citations
Preparation method of flame-retardant insulation board for building exterior wall
CN103553543A
Thermal mortar and preparation method thereof
CN108002775A
Thermal insulation panel
JP2004270378A
Thermal insulating slurry and method for its preparation
WO2021242106A1